Incidence, Predictors, and Outcomes of Patients Discharged Home Versus Other Medical Facility After Transcatheter or Surgical Aortic Valve Replacement. Issue 4 (4th July 2021) - Shreenivas, Satya; Lilly, Scott; Kodali, Susheel; Thourani, Vinod H.; Mack, Michael J.; Cohen, David J.; Arnold, Suzanne V.; Zhang, Yiran; Leon, Martin B.; Kereiakes, Dean J.
ABSTRACT: Background: Discharge patterns for patients following treatment of aortic stenosis with transcatheter (TAVR) or surgical aortic valve replacement (SAVR) are poorly defined and could impact long-term clinical outcomes. This study considers incidence, predictors, and outcomes of patients discharged home versus to another medical facility after either treatment. Methods: This is a retrospective analysis of the multicenter randomized PARTNER 2 trial of transcatheter versus surgical aortic valve replacement and associated registries. All patients who received either therapy and survived until discharge were included in two separate analyses: one for patients receiving TAVR and one for patients receiving SAVR. The primary outcome was 2-year mortality after discharge home versus other medical facility. Also, a model was developed to predict discharge patterns following TAVR or SAVR. Results: Of 4, 312 patients who underwent TAVR, 22% ( n = 958) were discharged to other medical facilities; 916 patients underwent SAVR and 52.4% ( n = 480) were discharged to other medical facilities. Two-year mortality for patients undergoing aortic valve replacement and discharged to other medical facility versus home was 36.6% vs 18.0% after TAVR ( p < 0.0001) and 19.7% vs 11.1% ( p < 0.001) after SAVR. Patients discharged to another medical facility had worse quality of life and were more likely to be readmitted after either procedure. Conclusion: After adjusting for risk factors that may relate to discharge location and death, discharge to other medical facility is associated with increased mortality and worse quality of life at 2 years following TAVR or SAVR treatment of aortic stenosis.